2009
DOI: 10.1097/aud.0b013e31818f359f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hearing Loss and Spectral Shaping on Identification and Neural Response Patterns of Stop-Consonant Stimuli in Young Adults

Abstract: Hearing loss, separate from aging, seems to negatively impact identification and neural representation of time-varying spectral cues like the F2 formant transition. Enhancing the audibility of the F2 formant transition cue relative to the rest of the stimulus does not overcome the effects of hearing loss on behavioral performance or neural response patterns in young adults. Thus, the deleterious effects of hearing loss on stop-consonant perception along the place-of-articulation continuum may not only be due s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…The authors proposed that the lack of significant hearing aid benefit might be due to factors beyond simple audibility, such as central auditory deficits or poorer cognitive ability. Harkrider, Plyler, and Hedrick (2009) reported that hearing loss, independent of aging, adversely affected underlying neural spectral cues and resulted in deficient consonant identification among hearing-impaired individuals. In a similar vein, they stated that compensation by improving audibility does not reduce the deleterious effects of hearing loss on consonant identification.…”
Section: Consonant Identificationmentioning
confidence: 99%
“…The authors proposed that the lack of significant hearing aid benefit might be due to factors beyond simple audibility, such as central auditory deficits or poorer cognitive ability. Harkrider, Plyler, and Hedrick (2009) reported that hearing loss, independent of aging, adversely affected underlying neural spectral cues and resulted in deficient consonant identification among hearing-impaired individuals. In a similar vein, they stated that compensation by improving audibility does not reduce the deleterious effects of hearing loss on consonant identification.…”
Section: Consonant Identificationmentioning
confidence: 99%
“…The sum was divided over the total number of transition steps for the continuum. Additionally, phonetic boundary locations associated with 50% points were computed for every psychometric function (e.g., Harkrider et al 2009). The 50% points were defined by converting the percent unshaped /b/ scores to scores and using linear least-squares fit to get an estimation of the 50% point which is the phonemic boundary of this phoneme.…”
Section: Methods Of Data Analysis Behavioral Data Analysismentioning
confidence: 99%
“…Spectral shaping reduced gain for low frequencies; and increased gain for mid and high frequencies, which is the frequency region of F2 transitions. Spectral shaping was determined by measuring 1/3 octave root mean square (RMS) levels in a Zwislocki coupler via a sound level meter with slow averaging and C-weighting (Harkrider et al 2009). …”
Section: Stimulimentioning
confidence: 99%
See 2 more Smart Citations